Accountability Of Perpetrators Of Corruption Criminal Acts For State Losses In The Use Of Customer Funds At Pt. Asuransi Jiwasraya : (Study of Cassation Decision Number 2931 K/Pid.Sus/2021) - Ferry Sabela; Farhana Farhana (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to analyze and explain the enforcement of criminal law against perpetrators of corruption for state losses at PT Asuransi Jiwasraya. As well as explaining the accountability of perpetrators of corruption for state losses in the use of customer funds at PT Asuransi Jiwasraya through Cassation Decision Number 2931 K / Pid.Sus / 2021 and government efforts to provide protection to customers or policyholders of PT. Asuransi Jiwasraya. This study employs a normative legal research methodology. The study's findings demonstrate that PT Asuransi Jiwasraya's criminal law enforcement is following the guidelines laid out in Law Number 31 of 1999, as revised by Law Number 20 of 2001, when it comes to prosecuting those responsible for causing state losses due to corruption. The formulation demonstrates the efficacy of current legal regulations in handling the Jiwasraya case and protects the interests of public investors and shareholders. It contains specific elements and is subject to a specific sentencing system. Corruption at PT Asuransi Jiwasraya has resulted in monetary losses for the state. This is due to the defendant's substantial acts, which satisfy the criteria for a